Nanofiltration membranes based on PA6/EVOH with variable composition and morphology. (9th January 2018) - Haddadpour, Nazanin; Ahmadi, Zahed; Shariatinia, Zahra; Afshari Taromi, Faramarz
Abstract : Nanofiltration PA6/EVOH membranes were prepared through a nonsolvent induced phase separation technique. The effects of polymer concentration in the solution and solvent evaporation time on the performance and morphology of the resulting membranes were investigated by cloud point titration, permeation, and scanning electron microscopy (SEM). Experimental cloud point data for various prepared membranes suggested that polymer solutions with higher concentrations of PA6/EVOH need a less content of nonsolvent. SEM observations show that an increase in polymer concentration leads to formation of a thin dense layer on the surface of the membrane thanks to pore size reduction. However, dense top layer of membrane becomes thicker as polymer concentration increases from 15 wt% to 20 wt%. The performance of membranes reveals a decrease with polymer concentration in casting solution. By contrast, Polyamide/Poly(ethylene‐co‐vinyl alcohol) membranes show an optimal performance with various formic acid evaporation times. J. VINYL ADDIT. TECHNOL., 25:E28–E34, 2019. © 2018 Society of Plastics Engineers